Talent Development and Employees' Performance in Public Universities - Kakkayi, Jolly Nyesigire; Mwazuna, Alice Ngele; Agaba, Moses; Munyambonera, Ezra (European Journal of Human Resource Management Studies, 2025)
This study examined the effect of talent development practices on employee performance in selected public universities in Uganda’s Western Region. The study was guided by Maslow’s Hierarchy of Needs Theory, and a convergent parallel mixed methods design was employed, integrating a cross-sectional survey of academic and administrative staff with key informant interviews. Both quantitative and qualitative data were collected from 320 respondents, which included both academic and administrative staff of the two selected public universities (Mbarara University of Science and Technology and Kabale University). Quantitative data was analyzed using structural modelling techniques, and qualitative insights were explored thematically. Findings indicated that talent development had a positive and significant effect on academic staff performance but had little effect on administrative staff performance. The study contributes to theory by extending Maslow’s Hierarchy of Needs through demonstrating how specific HRpractices, such as development, map onto esteem, safety and belonging needs in resource-constrained public universities. Practically, the study recommends talent development initiatives aligned with performance expectations, while underscoring the importance of leadership and responsive human resource systems in strengthening performance in public universities.